Clinical advantages of suctioning flexible ureteroscopy with intelligent pressure control on treating large upper urinary tract calculi - Cai, Weiping; Zheng, Bin; Li, Xinwei; Gao, Xingjian; Zhang, Zedong; Lu, Yijin; Zhao, Hualong; You, Junhong; Zheng, Gangfeng; Bao, Weilong; Lai, Yutong; Lv, Yisong (Frontiers in Surgery, 2025)
Suctioning Flexible Ureteroscopy with Intelligent Pressure Control (SFUI) has the advantage of automatically capturing and breaking urinary tract calculi while maintaining renal pelvic pressure stability. This retrospective study aimed to evaluate the efficacy of SFUI in treating upper urinary tract calculi of large sizes. A total of 200 patients with upper urinary tract calculi who underwent SFUI treatment in a single location from 2020 to 2021 were included. Outcomes were a one-session stone-free rate (SFR), one-month SFR, and complications within 4 weeks after SFUI classified by Clavien-Dindo grades. Patients’ median age was 50.0 years and a majority (65%) was males. Among them, 119 patients had small calculi (<2 cm) and 81 patients had large calculi (≥ 2 cm); 1 (0.8%) patient in the small calculi group, and 4 (4.9%) patients in the large calculi group had complications ≥ Grade II. Multivariable analysis showed that the large calculi group had significantly lower odds ratio for total one-session SFR [adjusted odds ratio (aOR): 0.22, 95% confidence interval (CI): 0.07–0.67, p = 0.008, S-value = 6.97] and one-month SFR (aOR: 0.27, 95% CI: 0.09–0.83, p = 0.022, S-value = 5.64) compared to the small calculi group, whereas calculi size was not associated with complication rate (aOR: 2.62, 95% CI: 0.23–29.32, p = 0.43, S-value = 1.20). In conclusions, SFUI is safe and effective for immediate stone removal after surgery. The very low complication rate benefits fast recovery, especially for patients with large calculi.